Determining the optimal method for creating nano-structured compositions based on polyester matrix having a permanent fire resistance - Reva, Ольга; Luk'yanov, Александр (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2015)
A method for fixing the inorganic non-toxic fire retardant compositions on the surface of the polyester materials by creating on the surface of polyester adhesive nanolayers. The optimal conditions for the pre-treatment of the polymer to provide a chemical interaction with inorganic modifier polyester matrix.